Wybrane problemy harmonizacji opodatkowania dochodów przedsiębiorstw - Marczakowska-Proczka, Joanna (Selected Problems of Harmonization Enterprises Income Taxation, 2009)
The article refers to directions of research connected with the EU enterprises income taxation. It presents arguments for speeding up research on enterprise income taxes harmonization, as well as arguments against this process. The EU previous law output on enterprises income tax harmonization was discussed
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 174-182